Critical dictionary on borders, cross-border cooperation and European integration - Medeiros, E. (European Planning Studies, 2021)
The world, and more particularly Europe, is marked by a strong presence of national borders which have substantial direct and indirect effects on the lives of millions of inhabitants, as the recent covidfencing process (Medeiros et al. 2021) has, once again, illustrated. Contrary to common assumptions, border regions can cover a relatively large portion of continents and spaces such as in the European Union. EU internal border regions cover approximately 40% of the EU territory, whilst accounting for roughly 30% of the EU population (150 million people). Ultimately, this vast border space produces 30% of the EU's GDP and hosts almost 2 million cross-border commuters. These include around 1.3 million cross-border workers (EC 2017). Understandably, the context of the territorial relevance of these borders justifies and reflects emerging research on border studies. Indeed, in Europe and North America, for instance, border studies have permeated the academic discourse in an increasing manner.